Does Metaphyseal Cement Augmentation in Fracture Management Influence the Adjacent Subchondral Bone and Joint Cartilage?. Issue 3 (January 2015) - Goetzen, Michael; Hofmann-Fliri, Ladina; Arens, Daniel; Zeiter, Stephan; Stadelmann, Vincent; Nehrbass, Dirk; Richards, R. Geoff; Blauth, Michael; Kellam., James Franklin
<x xml:space="preserve">Abstract</x> Abstract Augmentation of implants with polymethylmethacrylate (PMMA) bone cement in osteoporotic fractures is a promising approach to increase implant purchase. Side effects of PMMA for the metaphyseal bone, particularly for the adjacent subchondral bone plate and joint cartilage, have not yet been studied. The following experimental study investigates whether subchondral PMMA injection compromises the homeostasis of the subchondral bone and/or the joint cartilage. Ten mature sheep were used to simulate subchondral PMMA injection. Follow-ups of 2 (4 animals) and 4 (6 animals) months were chosen to investigate possible cartilage damage and subchondral plate alterations in the knee. Evaluation was completed by means of high-resolution peripheral quantitative computed tomography (HRpQCT) imaging, histopathological osteoarthritis scoring, and determination of glycosaminoglycan content in the joint cartilage. Results were compared with the untreated contralateral knee and statistically analyzed using nonparametric tests. Evaluation of the histological osteoarthritis score revealed no obvious cartilage damage for the treated knee; median histological score after 2 months 0 (range 4), after 4 months 1 (range 5). There was no significant difference when compared with the untreated control site after 2 and 4 months (P = 0.23 and 0.76, respectively). HRpQCT imaging showed no damage to the metaphyseal trabeculae. Glycosaminoglycan measurements of the treated joint cartilage after 4 months revealed no significant difference compared with the untreated cartilage (P = 0.24). The findings of this study support initial clinical observation that PMMA implant augmentation of metaphyseal fractures appears to be a safe procedure for fixation without harming the subchondral bone plate and adjacent joint cartilage.